Analisis Determinan Penyakit Hipertensi pada Anggota TNI yang Berumur dibawah 40 tahun di Rumah Sakit TK II Putri Hijau Medan - Nila Sari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Hypertension is one of the serious health problems. The World Health Organization (WHO) revealed that there were 839 million cases of hypertension in 2014, and it is estimated that there will have been 1.15 million cases in 2025. The data from Putri Hijau Level II Hospital showed that there were 226 cases of hypertension in the Indonesia soldiers in 2016. The objective of the research was to find out the determinants of hypertension in ≤ 40 year-old Indonesian soldiers at Putri Hijau Level II Hospital, Medan, in 2017. The research used observational analytic method with case-control study design. The samples were 44 respondents with hypertension in the case group and 44 respondents without hypertension in the control group. The result of multivariate analysis showed that consuming coffee (OR=15.514, 95%CI=4.275-56.297), consuming fat (OR=4.987 95%CI=1.380-18.021), smoking (OR=7,072 95%CI=1,344-37,209),and psychosocial stress (OR=4.858 95%CI=1.312-19,988) were the predictors of hypertension with the equation for hypertension of -4.510 + 2.742 (consuming coffee) + 1.607(consuming fat)+1.956 (smoking)+ 1.581 (psychosocial stress). It is recommended that the health care providers intensify promotion about healthy lifestyle, including quitting smoking, curbing fat and coffee consumption, and avoiding stress so that the risk for hypertension can be forestalled in the Indonesian soldiers as the persons who defend their nation.